Design and Performance of A Simple Solar Pump for Lift Irrigation Purposes - Girardier, M p; Clemot, Max G (Annals of Arid Zone, 2016)
This paper describes the performance studies carried out on a number of low temperature solar engines (LTS engines) ranging from 1 kw to 30 kw designed and developed by the Association Promethee, which includes the French Atomic Energy Commission (CEA) and Sofretes. These engines meant for pumping water will automatically pump water from any depth without any consumption of any kind of energy except that from the sun. As soon as the sun rises, the motor starts and the water flows until evening.The operating principle of these engines is opposite to that of a refrigerator. Water is heated in a battery of flat plate collectors and gives its heat through a heat exchanger to a low boiling point liquid like butane. The butane at a high pressure activate the piston of a engine and this butane at low pressure after going through the condenser (cooled by the pumped water of the well) is pumped back by the re-injection pump. The hydraulic pump coupled to the engine, lifts the water from the well. Calculations have shown that in the Sahel a 50 kw solar-energy station used for irrigation is competitive with electricity from the power grid as soon as the distance from the thermal power plant is over 60 kilometres.